Local Wisdom of Menegakgen Rumah Tradition at Tabuyung Village in Mandailing Natal - Harianja, Nurilam; Lubis, Tasnim (Tradition and Modernity of Humanity, 2023)
In its development, culture or tradition is born along with the community's needs in an environment. Thus, tradition will be the characteristic that distinguishes it from other regions. Furthermore, this growing tradition aims to unite the community and provide wise contributions to the community. And this is what is then called local wisdom. One tradition that is still maintained is Managakgen Rumah in Tabuyung village, Mandailing Natal district. The research method used in this study is qualitative, using descriptive methods, which describe phenomena that occur in the field. From the research results, it can be seen that this tradition contains a profound meaning about Gotong Royong. Through the Menagakgen tradition of this house, it strengthens the villagers' cohesiveness, brotherhood, and hospitality.